Differences Between the Recognition and Enforcement of Authentic Instruments and the Recognition and Enforcement of Judgments - Dymitruk, Maria; Gołaczyński, Jacek; Kaczorowska, Maria; Rodziewicz, Piotr (LeXonomica, 2021)
The subject of the article is to analyse and compare the specificity of judgments and authentic instruments in terms of cross-border recognition and enforcement under the Brussels I Recast Regulation framework. Particular focus has been put on the practical aspects of the definition of an authentic instrument. Selected detailed issues arising against this background have been discussed with reference to the Polish legal order as well as the case-law of the Court of Justice of the European Union (CJEU). Based on the undertaken considerations, some proposals have been formulated regarding the enhancement of the free circulation of authentic instruments within the European Union. Povzetek. Predmet članka je analiza in primerjava posebnosti sodnih odločb in verodostojnih listin z vidika čezmejnega priznavanja in izvrševanja v okviru prenovljene uredbe Bruselj I. Poseben poudarek je namenjen praktičnim vidikom opredelitve verodostojne listine. Izbrana podrobna vprašanja, ki se pojavljajo v tem kontekstu, so bila obravnavana s sklicevanjem na poljski pravni red in sodno prakso Sodišča Evropske unije (SEU). Na podlagi opravljene analize so bili oblikovani nekateri predlogi v zvezi z izboljšanjem prostega pretoka verodostojnih listin v Evropski uniji.